A Prospective Study of Adult Inguinal Hernia Repairs Implementing a New Technique Over A 5-year Period - Sharma, A P (Medical Journal of Shree Birendra Hospital, 1998)
A Prospective Study of Adult Inguinal Hernia Repairs Implementing a New Technique Over A 5-year Period